Total glucosinolate content of arugula (Eruca sativa Mill.) supplemented with rhizobacteria-enriched bio-slurry - Ariek Dwi Anggoro; Muhammad Wildan Abdillah; Ikhwan Adhirakha Mullatif; Regita Pramesti Widyaningrum; Kashifa Maria Jihan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Arugula is a member of Brassicaceae that has a high antioxidant content of glucosinolate. Bio-slurry is a kind of liquid fertilizer derived from sap of cow dung. Bio-slurry in combination with rhizobacterial can maximize decomposition and make nutrients more available. The research aimed to determine the total glucosinolate content in arugula due to the application of bio-slurry enriched with rhizobacteria. The study used a randomized complete block design with a single factor consisting of 9 levels, i.e., the combination of 3 types of rhizobacteria (Pseudomonas, Bacillus, Pseudomonas + Bacillus) and 3 doses of bio-slurry (0, 100, and 200 mL). The results showed that the application of Pseudomonas & Bacillus + 200 mL bio-slurry produced a higher antioxidant content than other inputs. The combination of bio-slurry fertilizer with rhizobacterial provides a higher ability than control to increase plant growth rates and the biosynthesis of glucosinolate. The optimal substitution for maximizing nutrient uptake in arugula growth was achieved with a bio-slurry dose of 200 mL, where the combined application of Pseudomonas and Bacillus strains enhanced plant growth and glucosinolate content. Keywords: antioxidant capacity; Bacillus; bacterial; biofertilizer; Pseudomonas